2014
DOI: 10.5014/ajot.2014.012419
|View full text |Cite
|
Sign up to set email alerts
|

Validating the Measurement of Executive Functions in an Occupational Context for Adults With Attention Deficit Hyperactivity Disorder

Abstract: OBJECTIVE. The objectives of this study were to better understand the cognitive profile of adults with attention deficit hyperactivity disorder (ADHD), their occupational performance, and their quality of life (QoL) and to examine the validity of a cognitive-functional evaluation (CFE) battery for these adults. METHOD. Eighty-one adults with ADHD and 58 without ADHD completed ADHD symptom ratings, the Behavior Rating Inventory of Executive Function-Adult Version, and the Adult ADHD Quality-of-Life Scale. An oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 42 publications
(58 reference statements)
2
16
0
Order By: Relevance
“…ADHD is a disorder that involves a deficit in behavioral inhibition, leading to problems with executive functioning (Boonstra, Oosterlaan, Sergeant, & Buitelaar, 2005). Stern and Maeir (2014) listed a range of difficulties in executive functions reported by individuals with ADHD, each of which exerts impact on job performance including postponement of assignments, difficulty prioritizing tasks, forgetting about appointments, problems with organizing work and planning, and difficulty making decisions. Given the experience of such deficiencies, individuals with ADHD may find it difficult to perform within the context of a regular work environment (Barkley & Murphy, 2010), and ADHD may thus impair the involvement in and continuation of a wage job.…”
Section: Adhd and Occupational Fitmentioning
confidence: 99%
“…ADHD is a disorder that involves a deficit in behavioral inhibition, leading to problems with executive functioning (Boonstra, Oosterlaan, Sergeant, & Buitelaar, 2005). Stern and Maeir (2014) listed a range of difficulties in executive functions reported by individuals with ADHD, each of which exerts impact on job performance including postponement of assignments, difficulty prioritizing tasks, forgetting about appointments, problems with organizing work and planning, and difficulty making decisions. Given the experience of such deficiencies, individuals with ADHD may find it difficult to perform within the context of a regular work environment (Barkley & Murphy, 2010), and ADHD may thus impair the involvement in and continuation of a wage job.…”
Section: Adhd and Occupational Fitmentioning
confidence: 99%
“…Attention deficit hyperactivity disorder (ADHD) is a neurodevelopmental disorder that is characterized by a pattern of behavior that can result in extensive difficulties in social, educational, or work environments (Stern & Maeir, 2014). These difficulties, as outlined in the Diagnostic and Statistical Manual of Mental Disorders (5th ed.…”
Section: Attention Deficit Hyperactivity Disorder and Sensory Processingmentioning
confidence: 99%
“…Although researchers of long-term studies have discussed the pervasiveness of ADHD in adulthood-with an estimated worldwide adult prevalence of between 2.5% and 4% (APA, 2013;Stern & Maeir, 2014)-little has been published with regard to sensory processing among adults. Gutman and Szczepanski (2005) found that children with ADHD and control groups differ considerably in terms of sensory processing.…”
Section: Attention Deficit Hyperactivity Disorder and Sensory Processingmentioning
confidence: 99%
“…It has been proposed that metacognition plays a larger role in these difficulties than behavior regulation problems. A larger focus on assessing how such impairments have an impact on occupational performance in everyday life has been proposed (Stern & Maeir, 2014). Such assessments could be a basis for a more comprehensive SAR and clarify the prognosis for the possibility to return to work.…”
Section: Discussionmentioning
confidence: 99%